2011
DOI: 10.1074/jbc.m111.224006
|View full text |Cite
|
Sign up to set email alerts
|

E2 Conjugating Enzyme Selectivity and Requirements for Function of the E3 Ubiquitin Ligase CHIP

Abstract: The transfer of ubiquitin (Ub) to a substrate protein requires a cascade of E1 activating, E2 conjugating, and E3 ligating enzymes. E3 Ub ligases containing U-box and RING domains bind both E2ϳUb conjugates and substrates to facilitate transfer of the Ub molecule. Although the overall mode of action of E3 ligases is well established, many of the mechanistic details that determine the outcome of ubiquitination are poorly understood. CHIP (carboxyl terminus of Hsc70-interacting protein) is a U-box E3 ligase that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 61 publications
(73 citation statements)
references
References 40 publications
(67 reference statements)
1
68
0
4
Order By: Relevance
“…CHIPUbc13-Uev1a may work sequentially with SCF ␤TrCP , whereby the SCF ligase initiates ubiquitination, and the CHIP enzyme complex carries out Lys 63 -linked polyubiquitination on an as yet unidentified substrate (56). It was recently shown that CHIP/Ubc13 can extend a monoubiquitinated protein and synthesize Lys 63 -linked chains on these ubiquitin moieties (17). As in the absence of Ubc13/CHIP, where GHR is ubiquitinated to the same extent as in clathrin-depleted cells, it might indicate that Ubc13/CHIP might edit pre-existing, ␤TrCP-derived, ubiquitin chains on GHR.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CHIPUbc13-Uev1a may work sequentially with SCF ␤TrCP , whereby the SCF ligase initiates ubiquitination, and the CHIP enzyme complex carries out Lys 63 -linked polyubiquitination on an as yet unidentified substrate (56). It was recently shown that CHIP/Ubc13 can extend a monoubiquitinated protein and synthesize Lys 63 -linked chains on these ubiquitin moieties (17). As in the absence of Ubc13/CHIP, where GHR is ubiquitinated to the same extent as in clathrin-depleted cells, it might indicate that Ubc13/CHIP might edit pre-existing, ␤TrCP-derived, ubiquitin chains on GHR.…”
Section: Discussionmentioning
confidence: 99%
“…CHIP can act together with either UbcH5a or Ubc13/UEV1a to assemble either Lys 48 -or Lys 63 -linked chains, respectively. In both cases, the interaction is between the U-box and the conserved SPA motif of the E2 enzymes (15)(16)(17). CHIP binds with its TPR domain to the COOH-terminal EEVD sequence of the molecular chaperones Hsp70 and Hsp90 (18).…”
Section: Growth Hormone Receptor (Ghr)mentioning
confidence: 99%
“…Ube2j1/Ubc6e has a transmembrane anchor and acts with RMA1 and HRD1 (29,43). Importantly, neither E2 functions with CHIP, which acts with Ube2d1/UbcH5a and Ube2n/ Ubc13 among others (44,45).…”
Section: E2-conjugating Enzyme Ube2g2mentioning
confidence: 99%
“…6A and B). The E2s UbcH5a and UbcH5b were selected for the in vitro reactions because they function with CHIP to mediate polyubquitination of other substrates (39,40). In vitro ubiquitination of His-MLK3 and His-CHIP autoubiquitination were observed in reaction mixtures that contained E1, E2, His-CHIP, His-MLK3, and ubiquitin ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, it has been proposed that a priming ubiquitination of the substrate by another E2 enzyme may be necessary for CHIP-Ubc13/Uev1a polyubiquitination to occur (39). Hence, for the analysis of CHIPmediated in vitro ubiquitination of MLK3 by Ubc13/Uev1a, we combined Ubc13/Uev1a with either Ube2W or Cdc34, both of which can monoubiquitinate substrates (40). All members of the UbcH5 family that were tested (UbcH5a, -b, -c, and -d) facilitated His-MLK3 ubiquitination by His-CHIP (Fig.…”
Section: Resultsmentioning
confidence: 99%